2021
DOI: 10.1111/maps.13748
|View full text |Cite
|
Sign up to set email alerts
|

Early diagenesis at and below Vera Rubin ridge, Gale crater, Mars

Abstract: Data returned by NASA’s Mars Science Laboratory Curiosity rover showed evidence for abundant secondary materials, including Fe‐oxides, phyllosilicates, and an amorphous component on and below Vera Rubin ridge in the Murray formation. We used equilibrium thermochemical modeling to test the hypothesis that altered sediments were deposited as detrital igneous grains and subsequently underwent diagenesis. Chemical compositions of the Murray formations’ altered components were calculated using data returned by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 101 publications
(257 reference statements)
1
23
0
Order By: Relevance
“…Previous workers (for example, Bristow et al., 2019; Fraeman et al., 2020; Frydenvang et al., 2020; Rampe et al., 2020; Turner et al., 2021) have suggested the presence of a diagenetic front, along the ridge, overlain by a relatively impermeable caprock. Such a model is broadly compatible with APXS compositional data from Jura_VRR (Thompson et al., 2020).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous workers (for example, Bristow et al., 2019; Fraeman et al., 2020; Frydenvang et al., 2020; Rampe et al., 2020; Turner et al., 2021) have suggested the presence of a diagenetic front, along the ridge, overlain by a relatively impermeable caprock. Such a model is broadly compatible with APXS compositional data from Jura_VRR (Thompson et al., 2020).…”
Section: Discussionmentioning
confidence: 96%
“…Phyllosilicates are also less abundant in GT drill sites on or in contact with the overlying pediment (Hutton, Edinburgh) (6-8 wt.%) (Thorpe et al, 2022), associated with areas of alteration (Section 4.3.2; also Thompson et al, 2022). Previous workers (for example, Bristow et al, 2019;Fraeman et al, 2020;Frydenvang et al, 2020;Rampe et al, 2020;Turner et al, 2021) have suggested the presence of a diagenetic front, along the ridge, overlain by a relatively impermeable caprock. Such a model is broadly compatible with APXS compositional data from Jura_VRR (Thompson et al, 2020).…”
Section: Relationship Of the Jura_gt To The Jura Member On Vrrmentioning
confidence: 99%
“…These diagenetic features are evidence for an extensive and longlived groundwater system that expands the window of habitability to the subsurface well after surface water retreated from the surface of Mars, due to the presence of redox-active elements (e.g., Fe, Mn, S), and elements required for life (e.g., S and P). Both early and late diagenetic events may have occurred to account for these observations (e.g., Turner et al, 2021).…”
Section: Accepted Articlementioning
confidence: 99%
“…Strata above Sutton Island (Blunts Point, Pettegrove Point, and Jura) likely represent lacustrine settings. The Pettegrove Point and Jura members have been overprinted by a later diagenetic event that may have formed the Vera Rubin ridge topographic feature (Edgar et al., 2020; Fraeman, Edgar, et al., 2020; Fraeman, Johnson, et al., 2020; Frydenvang et al., 2020; Rampe et al., 2020; Rivera‐Hernández et al., 2020; Thompson et al., 2020; Turner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation